Mecanismos de governança em plataformas de consumo colaborativo : um estudo experimental - Schiavini, Janaina Mortari (Universidade do Vale do Rio dos Sinos, 2019)
The phenomenon of collaborative consumption, that allows access instead of possesion of goods, and has been able to affect traditional businesses around the world. This is because people have relied on one another to make consumer decisions, especially in the context of the internet and digital platforms. However, these platforms present differences in management, governance and strategy when compared to formal-bureaucratic organizations. The value created by the community is the main source of competitive advantage and therefore a governance system is an essential competency for this type of business. However, research focused on the governance of platforms that emerge from collaborative consumption is still very limited. There is a research gap on the problem of cooperation in collaborative consumption, and studies about the mechanisms that influence this problem are needed. Based on these findings, the present study aimed to analyze the influence of different governance mechanisms (sanctions and communication) on cooperation and the moderating effects of disposition to trust and perceived risk in the context of collaborative consumption. Based on the theory of social dilemmas and research on collaborative consumption, the hypotheses of this research predicted that the introduction of governance mechanisms would increase cooperation and that communication would have a greater impact on cooperation than sanctions. In addition, it was hoped that the greater the disposition to trust, the greater the influence of communication on cooperation, and the less the disposition to trust, the greater the influence of sanctions. These were the central hypotheses of this paper, which were tested through experimental research with 223 participants. The results confirmed in parts the relations allowed in the hypotheses, indicating that: (1) sanctions and communication had the same effect on cooperation; (2) the disposition to trust negatively moderated the relationship between sanctions and cooperation and also the relationship between communication and cooperation; and (3) perceived risk moderated positively the relationship between sanctions and cooperation and the relationship between communication and cooperation. Regarding sanctions, these results are in line with previous studies, contributing to reinforcing the effectiveness of control and punishment in social dilemmas. Regarding communication, this paper contributes mainly to understand the conditions under which social dilemmas are solved in non-monetary platforms of collaborative consumption, showing that the transparency of the information about the interactions and the possibility of direct communication between the users of the platform also leverages cooperation, without the need for external controls and incentives, such as punishment. Finally, it is understood that the accomplishment of this study represents a relevant contribution to the knowledge of consumers attitudes towards governance in collaborative consumption, helping the platforms to promote better regulation of their communities. In addition, this research contributes for the construction of new conceptual models for governance in collaborative consumption, given the relevance of the phenomenon.
Keywords: Governança; Economia compartilhada; Consumo colaborativo; Dilemas sociais; Confiança; Governance; Sharing economy; Collaborative consumption; Social dilemas; Trust; ACCNPQ::Ciências Sociais Aplicadas::Administração